Flavopiridol, the first cyclin-dependent kinase inhibitor to enter the clinic: current status - Kelland, Lloyd R (Expert opinion on investigational drugs, 2000)
This review focuses on the clinical development of the prototype broad spectrum inhibitor of cyclin-dependent kinases (CDKs), flavopiridol, now undergoing Phase II single-agent trials and Phase I combination trials (with paclitaxel and cisplatin). Preclinically, flavopiridol is a potent inhibitor of CDKs 1, 2 and 4 in cell-free assays (IC50 in the region of 100 nM) and tumour cell growth in vitro (typical IC50 in the region of 100 nM). The drug showed in vivo antitumour activity (using iv., ip. or oral dosing) against a variety of human tumour xenografts, especially when administered on a regular daily, rather than weekly, schedule and most notably against prostate carcinoma, head and neck cancer, non-Hodgkin's lymphoma and leukaemia. The major toxicities observed in rodents were on the bone marrow and gastrointestinal tract. Pharmacokinetics were linear with dose and with a bi-exponential decline both in rodents and man. Oral bioavailability in rodents is in the region of 20%. Glucuronidation appears to be the major route of metabolism. Single-agent clinical trials have mainly used a 72 h continuous infusion schedule. Dose-limiting toxicities were diarrhoea and hypotension. Plasma concentrations in excess of those required for in vitro enzyme or cell growth inhibition are achievable. While there has been some evidence of single-agent antitumour activity (partial responses in a patient with renal cancer and another with gastric cancer), ongoing combination studies, especially with paclitaxel, where preclinical synergistic antitumour effects are observed, are promising. Doubt as to whether CDKs are the sole target responsible for the drug's antitumour effects have been raised by preclinical observations of apoptosis of non-cycling cells, effects on endothelial cells and non-CDK proteins, such as aldehyde dehydrogenase and glycogen phosphorylase, potent effects on PTEFb and transcription and its ability to directly interact with DNA.